Recognizing Autoimmune-Mediated Encephalitis in the Differential Diagnosis of Limbic Disorders - da Rocha, A.J.; Nunes, R.H.; Maia, A.C.M.; do Amaral, L.L.F. (American Journal of Neuroradiology, 2015)
SUMMARY: Limbic encephalitis is far more common than previously thought. It is not always associated with cancer, and it is potentially treatable. Autoantibodies against various neuronal cell antigens may arise independently or in association with cancer and cause autoimmune damage to the limbic system. Neuroimaging plays a key role in the management of patients with suspected limbic encephalitis by supporting diagnosis and excluding differential possibilities. This article describes the main types of autoimmune limbic encephalitis and its mimic disorders, and emphasizes their major imaging features.AMEautoimmune-mediated encephalopathyAMPARα-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acidCASPR2contactin-associated protein-like 2GAD6565-kD isoform of glutamic acid decarboxylaseGABAgamma-aminobutyric acidHSEherpes virus encephalitisLElimbic encephalitisLGI1leucine-rich glioma inactivated 1PLEparaneoplastic limbic encephalitisTLtemporal lobeVGKCvoltage-gated potassium channel